La experiencia con la metodología de aprendizaje basado en proyectos en cursos de inglés con fines específicos de la escuela de secretariado profesional de la universidad nacional - Marta Matamoros Blanco (rESPaldo: Revista Internacional en Administración de Oficinas y Educación Comercial, 2019)
the application Project Based Learning (PBL), a non-traditional methodology inteaching at some English courses with specific purposes (ESP) of the school ofProfessional Secretariat of Universidad Nacional de Costa Rica. To implementthis new methodology, we considered it necessary to conduct an assessmentof the process through research in the classroom and evaluate the results after Revista Internacional de Administración de Oficinas y Educación ComercialISSN: 1659-3464; Volumen 4, Número 1, Año 2019; pp. 1-18Marta Matamoros Blanco Artículo protegido por Licencia Creative Commons:doi: https://doi.org/10.15359/respaldo.4-1.22applying the methodology for three periods of class in some ESP courses. The study was conducted using a mixed approach based on opinions of the students collected through questionnaires, assessment instruments, and data analysis. Comparing the results in the three periods it is valued how the application of the methodology has impacted on the learning process of the students. In addition, the proposal aims to strengthen the activity that takes place in the classrooms, improve the learning processes of the students, and innovate in the work of university teaching.